Hot Steep Malt Sensory Evaluation Method combined with Check-All-That-Apply – an approach for barley (Hordeum vulgare L.) malt characterisation and quality control? - Häge, Doris; Baumgartner, Felix; Lindemann, Bernd (BrewingScience, 2025)
The Hot Steep Malt Sensory Evaluation, a method approved by the American Society of Brewing Chemists, was combined with the Check-All-That-Apply (CATA) method to assess the flavour profile of brewing malt. Ancient spring barley varieties (Hordeum vulgare L.), including Mahndorfer Hanna, Kraffts Riedgerste, and Alpine Pfauengerste, alongside a modern spring barley variety from the 2020 harvest, were malted with a standardised, small-scale malting process. Kilning was performed to produce Pilsner pale malt. The results of this study demonstrate that the Hot Steep Malt Sensory Evaluation, in conjunction with the CATA method, is an effective tool for differentiating the flavour characteristics of brewing base malt due to its simplicity and rapid execution. Both methods also proved to be suitable for detecting off-flavours in base malt. However, successful implementation requires the identification of relevant attributes and sensory training of panellists. Consequently, these methods are highly applicable for quality control within malt houses and breweries to assess malt quality. Both methods combined might improve quality control even in small-scale breweries.